1971
DOI: 10.1042/cs0400039
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Isotopically Labelled Vitamin D3 in Man: The Influence of the State of Vitamin D Nutrition

Abstract: S U M M A R Y1. The metabolism of radioactive vitamin D, has been studied in individuals low or deficient in vitamin D (group I) and in vitamin D treated subjects (group 11).2. In group I there was a smaller serum pool of vitamin D, turning over more rapidly than in group 11. The principal metabolite, peak IV, appeared more rapidly in the serum of group I ; the level of radioactivity attained in this and in the more polar metabolites, peak V and VI, was also higher than in group 11. Peak VI was the major radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0
2

Year Published

1972
1972
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(60 citation statements)
references
References 18 publications
6
52
0
2
Order By: Relevance
“…Patients on regular hemodialysis have almost similar levels of 25-OH-D3 in their serum as the investigated normal volunteers. These results correlate very well with findings reported in earlier investigations, where it could be demonstrated that the conversion of radioactive vitamin D 3-tracer to radioactive 25-OH-D3 is not influenced by the uremic state [20,[36][37][38][39][40]. The finding that the patients of groups II and III (serum creatinine between 4.0 and 12.0 mg%) reveal a significantly lower 25-OH-D3 level cannot, therefore, be interpreted as meta bolic disorder, but rather as consequence of a special dietetic regimen -low protein diet -, which is characterized, besides other factors, by a restriction of the usual nutritional sources of vitamin D (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…Patients on regular hemodialysis have almost similar levels of 25-OH-D3 in their serum as the investigated normal volunteers. These results correlate very well with findings reported in earlier investigations, where it could be demonstrated that the conversion of radioactive vitamin D 3-tracer to radioactive 25-OH-D3 is not influenced by the uremic state [20,[36][37][38][39][40]. The finding that the patients of groups II and III (serum creatinine between 4.0 and 12.0 mg%) reveal a significantly lower 25-OH-D3 level cannot, therefore, be interpreted as meta bolic disorder, but rather as consequence of a special dietetic regimen -low protein diet -, which is characterized, besides other factors, by a restriction of the usual nutritional sources of vitamin D (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…Since it has been demonstrated both in rats (29) and humans (30) (34), among others, the potential for altered vitamin D metabolism in many clinical situations is apparent. Therefore, patients on high doses of drugs known to stimulate hepatic drug-metabolizing enzymes, especially those individuals with marginal dietary intake or diseases predisposing to vitamin D malabsorption, should be carefully evaluated for evidence of vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In deficient humans treatment with vitamin D results in the fast appearance of 25OHD in the serum, which is maximal after few days, and much faster than in vitamin D replenished humans [76]. In non-deficient humans intervention studies have shown that supplemental vitamin D (25, 250 and 1,250 Ìg daily for 8 weeks) and 25OHD (10, 20 and 50 Ìg daily for 4 weeks) increase the net absorptive capacity of calcium in a dose-dependent manner; however, also in humans the effect of vitamin D 3 appears to be explainable by conversion to 25OHD, and not by increases in circulating 1,25(OH) 2 D [4].…”
Section: Biological Activitymentioning
confidence: 99%